Study of Malaysia’s challenges in Asia international business environment - Yaw, Wong Kok (IJRDO - Journal of Business Management, 2017)
Malaysia is one of the developing countries in Asia region which has formed the vision to become high income country by the end of year 2020. It is known as Wawasan 2020 which was introduced by the former Prime Minister, Tun Dr. Mahathir bin Mohamad. To achieve this aim, Malaysia has to make sure the achievement in all aspects of national development which included the political stability, economic expansion, business & socialcultural well-being and technologies & knowledge challenges. There are less than 5 years to achieve this objective. However, Malaysia is recently facing various challenges in Asia international business environment which shirking the foreign investors’ confidence on investment.